Economic Growth and Nonrenewable Resources: An Empirical Investigation - Ibrahim–Shwilima, Amos James (Asian Journal of Empirical Research, 2016)
In this paper, we revisit the resource curse hypothesis by focusing on the period after 1990. The study uses both cross-sectional and panel data techniques on a sample of 103 countries for the period 1995–2010. We find no strong evidence of the resource curse, after controlling for other important determinants of economic growth. The results show that nonrenewable resources are positively associated with economic growth for the period under study. Additionally, we find that public institutions measured using an index of government effectiveness are of paramount importance to economic growth. This suggests that if a resource-rich economy needs a greater contribution from its resources, it should improve the quality of institutions.